Steering labour migration to the EU - perspectives - Steffen Angenendt; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2008)
In July 2008, France will take on the EU Presidency. Insofar as the French government has made its goals for asylum and immigration policy known, the expectation is that it will concentrate on combating irregular immigration. This focus will likely fall short of the imperative set out by the European Union's heads of state and government for a 'comprehensive and coherent' policy. The question of labour migration from outside the Union is in particular danger of being neglected. This topic is a hot potato for all Member States. Many governments are concerned that common European rules will entail a loss of political control over immigration. Yet, it is precisely in this area that Europe-wide approaches could play a most fruitful role. How can a coherent and comprehensive European policy be fashioned that offers all the advantages of common rules without sapping sovereignty?
Keywords: 320